Spinel Magnetic Iron Oxide Nanoparticles: Properties, Synthesis and Washing Methods - Thomas Girardet; Pierre Venturini; Hervé Martinez; Jean-Charles Dupin; Franck Cleymand; Solenne Fleutot (Applied Sciences, 2022)
Nanoparticles have experienced increasing interest over the past three decades owing to the development of new synthesis methods and the adaptation of analysis tools with spatial resolutions below one micrometer. Among the different types of nanoparticles developed in recent years (metals, metal oxides, silica, polymers, etc.), significant scientific interest has developed around iron oxide nanoparticles. This review will focus on these magnetic iron oxide nanoparticles. We will first discuss the magnetic properties of iron oxide nanoparticles, then the different methods of synthesis and washing. Finally, we will discuss some functionalization strategies of iron oxide nanoparticles which are developed within our research team.